Potential health benefits of Cucurbita ficifolia: An updated review - Yadav, Dhananjay; Chauhan, Pallavi Singh; Mishra, Meerambika; Kwak, Minseok (Progress in Nutrition, 2020)
Plant-based medicines are widely used in the treatment of type 2 diabetes and its complications. Among them, pumpkin is one of the popular edible plants which are consumed as vegetables. Recent data suggested that pumpkin has significant medicinal properties that can be utilized in the therapy of diabetes and to lower down associated morbidity. The presence of unique natural edible substances in the pumpkin which includes phytochemicals and antioxidants. Several potential medical benefits such as hepatoprotective, anti-cancerous, antimicrobial, anti-inflammatory and antiulcer activities are also documented. The purpose of the present article is to discourse the antidiabetic potentials and lipid-lowering properties of pumpkin which may convey further research and a clinical trial with this plant for the betterment of mankind. Additionally, the review insight a short description on distribution, botanical and physical characteristics, ecology and nutritional values.